1979
DOI: 10.1111/j.1365-2672.1979.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Fluorescent Antibody Method and a Standardized Cultural Method for the Detection of Salmonellas

Abstract: The results of routine use of the indirect fluorescent antibody (FA) technique using the Spicer‐Edwards H antisera set are reported for a range of agricultural and food samples. The FA technique was used on samples after the pre‐enrichment incubation period in the proposed ISO method for isolation of salmonellas. The numbers of FA false positive samples (ca. 5% overall) and FA false negative samples (ca. 1·3%) were low, but some originally FA false positive results were later shown to be false negative cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The reports on the necessity for selective cultivation are controversial. Some detection methods allow the detection of Salmonella directly after cultivation in non-selective media Gibbs, Patterson, & Early, 1979;Löfström, Krause, Josefsen, Hansen, & Hoorfar, 2009;Matias et al, 2010;Tatavarthy et al, 2009). However, several case studies have shown that selective enrichment cultivation enhances the accuracy of molecular detection (Myint, Johnson, Tablante, & Heckert, 2006;Upadhyay et al, 2010).…”
Section: Background Microbiotamentioning
confidence: 99%
“…The reports on the necessity for selective cultivation are controversial. Some detection methods allow the detection of Salmonella directly after cultivation in non-selective media Gibbs, Patterson, & Early, 1979;Löfström, Krause, Josefsen, Hansen, & Hoorfar, 2009;Matias et al, 2010;Tatavarthy et al, 2009). However, several case studies have shown that selective enrichment cultivation enhances the accuracy of molecular detection (Myint, Johnson, Tablante, & Heckert, 2006;Upadhyay et al, 2010).…”
Section: Background Microbiotamentioning
confidence: 99%